Influence of Compression Rings on the Dynamic Characteristics and Sealing Capacity of the Combustion Chamber in Diesel Engines (2021)
Internal combustion engines are widely implemented in several applications; however, they still face significant challenges due to the sealing capacity of the compression rings. Gas leakage through the crankcase, also known as blow-by, directly impacts power losses, overall efficiency, and global emissions. Therefore, the present study investigates the influence of parameters such as the ring gap, ring masses, and twist angle of the compression rings on the sealing capacity of the combustion chamber. A mathematical model is proposed to account for geometric, dynamic, and operational characteristics in a single-cylinder diesel engine. The results indicated that the greatest gas losses to the crankcase occur during the compression and combustion stages as a consequence of extreme pressure conditions. Specifically, at least 0.5% of the gases locked in the combustion chamber are released on each cycle, while increasing the mass of the compression rings boosts the gas leakage due to higher inertial forces in the rings. In contrast, a positive twist angle of the compression rings reduced the combustion gases leakage by 7.33 × 10−5 g/cycle. Additionally, a combined reduction in the gap of both compression rings minimized the leakage flows by 37%. In conclusion, the proposed model served as a robust tool to evaluate different parameters on the sealing capacity of the combustion chamber that contribute to minimizing global emissions. Secondary piston motion and ring distortion represent significant opportunities in future studies.